Early Childhood Education for Sustainability: Exploring the Barriers to Implementation and Arguing for a Transformative Approach - Bailey, Claire (2017)
Early childhood education for sustainability represents the confluence of two globally significant fields of research; early childhood education and education for sustainability. However, this hybrid field has yet to make the significant steps toward tackling the sustainability challenges faced by the world that UN institutions had claimed it would. This paper identifies and explores the reasons why implementation has been so difficult. Through this, it then offers recommendations as to what sort of approach would succeed, identifying a transformative education paradigm as being most appropriate.